2023
DOI: 10.1093/cid/ciad366
|View full text |Cite
|
Sign up to set email alerts
|

Sustained Viral Suppression With Dolutegravir Monotherapy Over 192 Weeks in Patients Starting Combination Antiretroviral Therapy During Primary Human Immunodeficiency Virus Infection (EARLY-SIMPLIFIED): A Randomized, Controlled, Multi-site, Noninferiority Trial

Abstract: Background Starting combination antiretroviral therapy (cART) during primary human immunodeficiency virus type 1 (HIV-1) infection results in a smaller HIV-1 latent reservoir, reduced immune activation, and less viral diversity compared to starting cART during chronic infection. We report results of a four-year study designed to determine whether these properties would allow sustained virological suppression after simplification of cART to dolutegravir (DTG) monotherapy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Encouragingly, DTG monotherapy has been shown to be robust to resistance evolution for at least 192 weeks. 52 However, treatment adherence was extremely high (>99%) in this cohort and these results may not hold in other settings.…”
Section: Discussionmentioning
confidence: 64%
“…Encouragingly, DTG monotherapy has been shown to be robust to resistance evolution for at least 192 weeks. 52 However, treatment adherence was extremely high (>99%) in this cohort and these results may not hold in other settings.…”
Section: Discussionmentioning
confidence: 64%
“…DTG monotherapy (Scenario 6) : Table 4 also summarizes data from four clinical trials of DTG monotherapy that enrolled 276 PLWH with VS for six or more months [ 115 , 116 , 117 , 118 , 119 , 120 , 121 ]. The proportion with a history of receiving an INSTI ranged from 15% and 17% in DOMONO and DOLAM to 60% in EARLY SIMPLIFIED and 100% in MONCAY.…”
Section: Resultsmentioning
confidence: 99%
“…Of note, there was an absence of viral evolution, reflecting the emergence of drug resistance in the viral reservoir, as assessed in the proviral DNA from peripheral blood mononuclear cells [ 22 ]. This trend continued for 96 weeks, with 64 out of 64 patients maintaining a virological response in the dolutegravir monotherapy group and 30 out of 30 patients in the cART group [ 24 ]. Remarkably, at the study’s endpoint on week 192, there were no instances of virological failure reported in either group, demonstrating the non-inferiority of dolutegravir monotherapy as a simplification strategy [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…This trend continued for 96 weeks, with 64 out of 64 patients maintaining a virological response in the dolutegravir monotherapy group and 30 out of 30 patients in the cART group [ 24 ]. Remarkably, at the study’s endpoint on week 192, there were no instances of virological failure reported in either group, demonstrating the non-inferiority of dolutegravir monotherapy as a simplification strategy [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation